2008
DOI: 10.1038/nnano.2008.365
|View full text |Cite
|
Sign up to set email alerts
|

Gram-scale production of graphene based on solvothermal synthesis and sonication

Abstract: Carbon nanostructures have emerged as likely candidates for a wide range of applications, driving research into novel synthetic techniques to produce nanotubes, graphene and other carbon-based materials. Single sheets of pristine graphene have been isolated from bulk graphite in small amounts by micromechanical cleavage, and larger amounts of chemically modified graphene sheets have been produced by a number of approaches. Both of these techniques make use of highly oriented pyrolitic graphite as a starting ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
588
2
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,067 publications
(616 citation statements)
references
References 22 publications
18
588
2
8
Order By: Relevance
“…This solvothermal reaction method can deliver graphene yield of approx. 0.1 g per 1 mL of ethanol-typically yielding 0.5 g per reaction [37].…”
Section: Pyrolysis Methodsmentioning
confidence: 99%
“…This solvothermal reaction method can deliver graphene yield of approx. 0.1 g per 1 mL of ethanol-typically yielding 0.5 g per reaction [37].…”
Section: Pyrolysis Methodsmentioning
confidence: 99%
“…But as for supercritical fluid extraction, it was observed that the high temperature and pressure resulted in chemical alteration of the extracted pollutants in some instances [22]. An alternative approach may be explored to use solvothermal process [23], which is usually conducted at lower temperature and pressure in comparison with supercritical fluid extraction. To our knowledge, only limited works focused on the application of this procedure for cleaning up organic pollutants [24].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the Raman spectra of both S‐SG and pristine SG showed broad and merged disorder‐induced D‐bands and graphite G‐bands at around 1350 and 1600 cm −1 (Figure 2c). In the X‐ray diffraction (XRD) results (Figure 2d), broad peaks located at 22.3° and 44.3° were observed for both S‐SG and the pristine SG, corresponding to the (002) diffraction of the graphitic layered structure and the (100) diffraction of graphite, respectively 3, 9, 11. Broad and diffuse ring patterns are observed in selected area electron diffraction patterns of S‐SG and pristine SG (Figure S3, Supporting Information), confirming that a stacking number of carbon layers in S‐SG and pristine SG is smaller than that of graphite.…”
mentioning
confidence: 99%